Joint meeting of the Labour and Socialist International, International Federation of Trade Unions, representatives of British and French industrial and labour movements, London, 24th January, 1939 (statement) - International Federation of Trade Unions
1939-01-25 017b-0025-001 292/946/17b/26(i)